Climate Change Policy: Mixing Politics and Uncertainty - Marriott, Dean (Maine Policy Review, 1993)
Global climate change has garnered some media attention, but has failed to gather the attention of most governmental decision makers and the public. In an effort to advance concerns about the issue, the New England Governors and Eastern Canadian Premiers sponsored a three-day symposium on climate change last May 19-21 in Portland. At the symposium, scientists and public officials from both the U.S. and Canada explored the science of climate change, the potential implications and impact of climate change on this region, and the possible policy responses. Dean Marriott [and James Bruce and Mark Victor, this issue] reflecting the breadth of topics explored at the symposium, argues that the level of public and public policy decision makers’ awareness about climate change issues must be heightened, and decision makers must begin to deal collaboratively with the many serious challenges climate change is presenting to the region.